Influence of electrolyte imbalance on regional wall motion abnormalities in STEMI patients of North Indian origin - Shiraz Rizvi, S. Mohd.; Sunny, Sini; Wani, Irshad A.; Mahdi, Farzana; Zaidi, Zeeshan H.; Rajasekaran, Namakkal S. (Frontiers in Cardiovascular Medicine, 2023)
Assessing regional wall motion abnormalities (RWMA) in the myocardium may provide early diagnosis and treat chronic remodeling in STEMI patients. We assessed RWMA in 217 subjects with anterior STEMI admitted to Era University Hospital in Lucknow, UP, India. Besides abnormalities in the LAD territory, sub-sets of patients exhibited diffuse regional myocardial dysfunction. Interestingly, variations in serum electrolytes, specifically sodium and potassium, significantly affected the distribution and frequency of RWMA. Notably, RWMA occurred in the basal septum, apical septum, apex, and lateral wall in the anterior STEMI group. Additionally, the rate of regional dysfunction varied with serum urea and creatinine levels. This suggests that anterior STEMI can manifest myocardial abnormalities beyond the LAD territory. These findings indicate that ST-segment elevation might not be specific, possibly influenced by electrolyte changes affecting cardiac rhythm. Therefore, diagnosing and correcting region-specific wall motion abnormalities and electrolyte imbalances may improve outcomes in STEMI patients.